2004
DOI: 10.1167/iovs.03-1392
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apoptosis Markers in the Retinas of Human Subjects with Diabetes

Abstract: Ganglion cells in diabetic retinas express several proapoptosis molecules, suggesting that these cells are the most vulnerable population. Glial cells in diabetic retinas are activated and express several antiapoptosis molecules in addition to the cytotoxic effector molecule FasL, suggesting a possible role of glial cells in induction of apoptosis in ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
174
1
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(201 citation statements)
references
References 56 publications
13
174
1
13
Order By: Relevance
“…Postmortem human diabetic retinas exhibit increased markers of apoptosis in ganglion cells (44). Animal studies show accelerated apoptosis of retinal neurons (45,46), glial activation (47-49), impaired glial cell metabolism (50 -52), and microglial cell activation (11,53,54).…”
Section: Fig 2 Functional Anatomy Of the Retina Metabolic Interactmentioning
confidence: 99%
“…Postmortem human diabetic retinas exhibit increased markers of apoptosis in ganglion cells (44). Animal studies show accelerated apoptosis of retinal neurons (45,46), glial activation (47-49), impaired glial cell metabolism (50 -52), and microglial cell activation (11,53,54).…”
Section: Fig 2 Functional Anatomy Of the Retina Metabolic Interactmentioning
confidence: 99%
“…In a previous study, we demonstrated that ganglion cells in diabetic retinas expressed the apoptosispromoting factors caspase-3, Fas, and Bax, suggesting that these cells are the most vulnerable population. 9 A number of additional mediators that are either antiapoptotic or proapoptotic have been identified. 10 They include among others the serine/threonine protein kinase Akt (also known as protein kinase B), cyclooxygenase-2 (Cox-2), Mcl-1, Bcl-2-associated death promoter (Bad), cytochrome c, apoptosis-inducing factor (AIF), tumour necrosis factor receptor-1-associated death domain protein (TRADD), and Fas-associated death domain protein (FADD).…”
mentioning
confidence: 99%
“…These findings corroborate experimental data which suggest that neuronal apoptosis in the retina is an early and persistent event in diabetes (Abu‐El‐Asrar et al. 2004; Barber et al. 2011).…”
Section: Introductionmentioning
confidence: 99%